2019
DOI: 10.1080/08870446.2019.1644335
|View full text |Cite
|
Sign up to set email alerts
|

Editor choice: Let it rest: Sleep and health as positive correlates of forgiveness of others and self-forgiveness

Abstract: Objective: The present study examined forgiveness of others, self-forgiveness, sleep, and health in a nationally representative sample of United States adults. It was hypothesised that sleep would mediate the associations of forgiveness of others and self-forgiveness with health. Design: A nationally representative sample of 1,423 United States adults participated in a survey. Main Outcome Measures: Measures included forgiveness of others, self-forgiveness, sleep quantity, sleep quality, psychological distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 62 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…As might be expected, DF correlates with measures of religion (e.g., Bassett, Carrier, Charleson, et al, 2016; Walker & Gorsuch, 2002) and spirituality (e.g., Lyons, Deane, Caputi, & Kelly, 2011). In fact, national surveys show that DF is related not only to being religiously affiliated (Toussaint & Williams, 2008), but also to levels of religiosity (e.g., Escher, 2013; Toussaint & Williams, 2008). There is also evidence to show how prayer that includes asking for God’s forgiveness predicts interpersonal forgiveness and relationship healing (Wuthnow, 2000).…”
Section: Research On Divine Forgivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…As might be expected, DF correlates with measures of religion (e.g., Bassett, Carrier, Charleson, et al, 2016; Walker & Gorsuch, 2002) and spirituality (e.g., Lyons, Deane, Caputi, & Kelly, 2011). In fact, national surveys show that DF is related not only to being religiously affiliated (Toussaint & Williams, 2008), but also to levels of religiosity (e.g., Escher, 2013; Toussaint & Williams, 2008). There is also evidence to show how prayer that includes asking for God’s forgiveness predicts interpersonal forgiveness and relationship healing (Wuthnow, 2000).…”
Section: Research On Divine Forgivenessmentioning
confidence: 99%
“…Sex differences in feeling forgiven by God exist. Compared with men, women report higher levels of DF (Chou & Liska, 2013; Hayward & Krause, 2013; Toussaint & Williams, 2008). In a Mormon sample, birth order was related to DF with first-borns seeing God as more forgiving (Chou & Liska, 2013).…”
Section: Research On Divine Forgivenessmentioning
confidence: 99%
“…Recent research showed that at the trait level, people who were more forgiving also slept better ( Toussaint et al, 2019 ). Other research found that the forgiveness and sleep relationship was mediated by lower levels of rumination and negative affect ( Stoia-Caraballo et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 Better baseline sleep quality and sleep quantity would have a significant inverse relationship with trait rumination and negative affect in accordance with research by Mellman (2006) , but a direct relationship with trait self-regulation, forgiveness, and flourishing in the past month. The latter hypotheses extend from research on sleep and its beneficial associations with self-regulation ( Barber et al, 2013 ), emotion regulation ( Palmer and Alfano, 2017 ; Vandekerckhove and Wang, 2018 ), emotional processing ( Tempesta et al, 2018 ), forgiveness ( Toussaint et al, 2019 ), and quality of life ( Léger et al, 2001 ).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation